Effect of dynamic and operational restrictions in the energy management strategy on fuel cell range extender electric vehicle performance and durability in driving conditions. (15th August 2022) - Desantes, J.M.; Novella, R.; Pla, B.; Lopez-Juarez, M.
Highlights: FCREx dynamic & operation limits effect on performance & durability was evaluated. Performance and durability for FCREx vehicles in driving cycle were correlated. Maximum lifetime (+110%) was achieved with |di/dt|max  = 0.01 A/cm 2 s imin  = 0.15 A/cm 2 . |di/dt|max  = 0.001 A/cm 2 s or imin  = 0.2 A/cm 2 do not allow charge-sustained mode. Recommendations for FCREx vehicle and FC stack manufacturers were elaborated. Abstract: Aiming at increasing fuel cell (FC) stack durability in driving conditions, part of the scientific community has focused its efforts on developing energy management strategies (EMS) for fuel cell hybrid vehicles (FCV). Nonetheless, most of these studies do not explicitly explain the effect of constraining the EMS in both degradation and performance when acting on the FC system dynamics or operational space nor consider the FC range-extender (FCREx) architecture for passenger car application. This study evaluates the potential of FCREx architecture to maximize FC stack durability and performance through control strategy dynamic and operational space limitations. For that purpose, a FCV modeling platform was developed and integrated together with an EMS optimizer algorithm and a semi-empirical advanced FC stack degradation model for driving cycle conditions. The resulting modeling platform was then simulated in WLTC 3b driving cycle to predict FC degradation and H2 consumption with different dynamic and operational restrictions. Practical limits for EMS constraining were identified as —di/dt—max  = 0.001 A/cm 2 s or imin  = 0.2 A/cm 2 since they prevented the EMS from fulfilling the constant state-of-charge constraint in high-dynamic driving condition. In this sense, —di/dt—max  = 0.01 A/cm 2 s and imin  = 0.15 A/cm 2 were recommended as the combination of constraints that maximizes FC stack durability (+110%) without affecting the FCV operability with only an increase in of 4.7% in H2 consumption. From these results, a set of recommendations and guidelines for FCREx vehicle manufacturers and FC stack developers were elaborated based on the benefits of understanding the dynamics and operational constraints that the FC system is going to be subjected to under real operation.